Efficiency of the bicycle operation under various tactical variants - Колумбет, Олександр Миколайович; Колумбет, О. М.; Колумбет, Александр Николаевич; Kolumbet, Oleksandr M.; Kolumbet, A. N.; Базилюк, Тетяна Антонівна; Базилюк, Т. А.; Базилюк, Татьяна Антоновна; Bazyliuk, Tetiana A.; Bazulyuk, T. A.; Дудорова, Людмила Юріївна; Дудорова, Л. Ю.; et al. (IP Iermakov S. S., 2017)
Aim: to determine the efficiency of the cyclist in various tactical options. Material: In the experiments participated athletes (n = 6) of high qualification (mean age - 19.8 ± 1.3 years, mean weight - 71.4 ± 3.5 kg). As a model of the individual pursuit race at 4 km, a five-minute pedaling on the bicycle ergometer was used. Series of loads was set on the modernized mechanical bicycle ergometer “Monark” . The five-minute bicycle ergometer test is similar to the individual pursuit race at 4 km: according to the time of the exercise; on the frequency of pedaling (110-120 rpm); on the frequency of heartbeats. Results: Tactical variants in the pursuit race at 4 km are considered. The total work in a free test was on average 106.38 ± 3.57 kJ. The operating energy consumption is on average for 379.0±16.1 kJ. The operating efficiency (economy) of the exercise attained on average for 28.0 ± 0.75%. This corresponds to the effectiveness of aerobic work of moderate power. The ratio of aerobic and anaerobic contributions to the provision of work was 77.3 and 22.7%. The smallest work was done in a test with step-increasing power. The athletes performed the closest work to the given job in the test with a variable (±15%) operating mode. The shortfall in it was on average for 0.46%. The absence of reliable differences in the economics of the work did not allow us to identify a rational variant of power distribution for an exercise lasting 5 minutes. Conclusions: Tactical options in the pursuit race for 4 km depend on the features of the power systems of the rider. When optimizing tactics, it is necessary to select an individually optimal variant of the distribution of forces at a distance.

Мета: визначити працездатність велосипедиста в різних тактичних варіантах. Матеріал: У дослідах брали участь спортсмени (n = 6) вищої кваліфікації (середній вік – 19,8 ± 1,3 року, середня вага – 71,4 ± 3,5 кг). Як зразок індивідуальної гонки переслідування на 4 км було використано п’ятихвилинне обертання педалей на велоергометрі. Серія навантажень була встановлена ​​на модернізованому механічному велоергометрі «Монарк». П’ятихвилинна велоергометрична перевірка схожа на індивідуальну гонку переслідування на 4 км: за часом виконання вправи; за частотою обертання педалей (110-120 об/хв); на частоту серцевих скорочень. Результати: Розглянуто тактичні варіанти в гонці переслідування на 4 км. Загальна робота у вільному тесті склала в середньому 106,38 ± 3,57 кДж. Експлуатаційні витрати енергії в середньому становлять 379,0±16,1 кДж. Ефективність (економічність) вправи досягла в середньому 28,0 ± 0,75%. Це відповідає ефективності аеробної роботи середньої потужності. Співвідношення аеробних та анаеробних внесків у забезпечення роботи становило 77,3 та 22,7 %. Найменшу роботу виконано в тесті зі ступінчастим збільшенням потужності. Найближчу до заданої роботи спортсмени виконали в тесті зі змінним (±15%) режимом роботи. Нестача в ньому становила в середньому 0,46%. Відсутність достовірних відмінностей в економіці роботи не дозволила визначити раціональний варіант розподілу потужності для вправи тривалістю 5 хвилин. Висновки: Тактичні варіанти в гонці переслідування на 4 км залежать від особливостей силових систем гонщика. При оптимізації тактики необхідно підібрати індивідуально оптимальний варіант розподілу сил на відстані.
Kolumbet A. N. Efficiency of the bicycle operation under various tactical variants / A. N. Kolumbet, T. A. Bazulyuk, L. Y. Dudorova, S. M. Chernovsky, N. Y. Maximovich // Physical Education of Students. - Vol. 21. – Iss. 5. - IP Iermakov S. S., 2017. – P. 219-224.
Keywords: cycling; tactics; energy expenditure; economy; їзда на велосипеді; тактика; енерговитрати; економіка; Research Subject Categories::INTERDISCIPLINARY RESEARCH AREAS::Sports